2008
DOI: 10.1177/0363546508316773
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Chronic Osteochondral Lesions of the Talus

Abstract: Arthroscopic treatment of chronic symptomatic osteochondral lesions of the talus results in good clinical outcomes in the majority of patients. However, pain and functional limitation may persist in some patients, especially those noted to have unstable osteochondral defects at the time of arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
385
3
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(419 citation statements)
references
References 54 publications
23
385
3
8
Order By: Relevance
“…The use of either CT or MRI is recommended for the diagnosis of OCD, but as the subchondral bony defect is the main problem in ankle lesions, 434 CT scans are preferred for preoperative planning because they accurately assess the size of the bony fragment or associated cyst. 129,160 With anterior ankle arthroscopy, vision of only the anterior part of the OCD is initially required. 432 After identification of the anterior border of the defect, it is debrided anteriorly to posteriorly to further expose the defect, followed by microfracturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of either CT or MRI is recommended for the diagnosis of OCD, but as the subchondral bony defect is the main problem in ankle lesions, 434 CT scans are preferred for preoperative planning because they accurately assess the size of the bony fragment or associated cyst. 129,160 With anterior ankle arthroscopy, vision of only the anterior part of the OCD is initially required. 432 After identification of the anterior border of the defect, it is debrided anteriorly to posteriorly to further expose the defect, followed by microfracturing.…”
Section: Discussionmentioning
confidence: 99%
“…129,160 Th e range of motion of the ankle joint has been successfully analyzed using stress CT with forced extreme positions in healthy individuals. 402 Using a similar scanning technique in patients with an OCD, van Bergen et al showed that the location of talar OCDs on CT scans of the ankle in full…”
mentioning
confidence: 99%
“…This is promising as other osteochondral defect treatments with scaffold only [4,8,14] result in the predominant formation of fibrocartilage, which possesses inferior biomechanical properties [6] and would translate to a shorter repair tissue life span [3].…”
Section: Discussionmentioning
confidence: 99%
“…Ferkel et al [18] found deterioration of clinical scores in up to 35% of patients within 5 years following BMS. Lee et al [19] reported that only 30% of patients had integration of the repair tissue with the surrounding native cartilage at second look arthroscopy 12 months after BMS.…”
Section: Reparative Proceduresmentioning
confidence: 98%
“…Despite successful outcomes following BMS for OLT, it is of increasing concern that deterioration of reparative fibrous cartilage tissue is inevitable over time [18][19][20]. Ferkel et al [18] found deterioration of clinical scores in up to 35% of patients within 5 years following BMS.…”
Section: Reparative Proceduresmentioning
confidence: 99%